1978
DOI: 10.1002/1097-0142(197808)42:2<490::aid-cncr2820420217>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

LDH isoenzyme patterns in human gastric mucosa with precancerous changes

Abstract: By using an original method of electrophoresis separation, the normal relative values of each one of the LDH isoenzymes in the gastric body and antral mucosa were determined. It has been shown in gastric tumors that there is a significance rise in the relative values of "type M" isoenzymes (iso-LDH-4-5). With intestinal metaplasia as well as gastritis, a significant elevation of the relative value of iso-LDH-5 has been demonstrated in the antral mucosa. In 6 benign gastric polyps we found a similar disturbance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In this study, the CG rat model was established by ethanol. Ethanol has been widely used to induce CG in experimental animals via interference with the secretion of cyclooxygenase, lactate dehydrogenase, cytokines and oxyten‐derived free radicals in the gastric mucosa, which directly or indirectly damages the gastric mucosa (Al‐Quraishy et al, 2017; Carda‐Abella et al, 1978; Mustonen et al, 2007). The findings of our study provide useful reference for further pharmacological investigation in vivo , which may help to understand pharmacological mechanisms and clinical applications of BXXXD.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the CG rat model was established by ethanol. Ethanol has been widely used to induce CG in experimental animals via interference with the secretion of cyclooxygenase, lactate dehydrogenase, cytokines and oxyten‐derived free radicals in the gastric mucosa, which directly or indirectly damages the gastric mucosa (Al‐Quraishy et al, 2017; Carda‐Abella et al, 1978; Mustonen et al, 2007). The findings of our study provide useful reference for further pharmacological investigation in vivo , which may help to understand pharmacological mechanisms and clinical applications of BXXXD.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the reports of high levels of LDH IV/LDH-X in normal adult testes, Wampler & Hayra (1977) reported that LDH-1 was elevated in 2 patients with testicular tumours. Marshall et al (1979) and Carda-Abella et al (1978) have recorded changes in isoenzyme patterns in tumours arising at other sites. The 2 groups have suggested that the shift may be due to changes in metabolism in the tumour cells, possibly due to reduction in available oxygen in bulky tumours.…”
mentioning
confidence: 99%